2011
DOI: 10.1200/jco.2011.35.8135
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of High-Risk Myelodysplastic Syndrome After Azacitidine Treatment Failure

Abstract: Purpose Azacitidine (AZA) is the current standard of care for high-risk (ie, International Prognostic Scoring System high or intermediate 2) myelodysplastic syndrome (MDS), but most patients will experience primary or secondary treatment failure. The outcome of these patients has not yet been described. Patients and Methods Overall, 435 patients with high-risk MDS and former refractory anemia with excess blasts in transformation (RAEB-T) were evaluated for outcome after AZA failure. The cohort of patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
351
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(372 citation statements)
references
References 28 publications
15
351
3
3
Order By: Relevance
“…The observation that higher BM blast count was a poor predictor for survival and that there was a poor response rate to intensive chemotherapy (CTx) for sAML with a prior history of HMA prompted us to investigate the role of active treatment in patients with sAML evolving from MDS-HTF (sAML/ MDS-HTF). 8,9 None of the prior studies have analyzed the impact of SCT on the survival of patients with sAML/MDS-HTF, although one group reported a poor outcome in patients with HTF in whom AZA was administered for sAML. 10 The aim of the present study was to evaluate the influences of therapeutic modalities on the survival of patients with sAML/MDS-HTF by analyzing clinical outcomes according to the treatment option.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that higher BM blast count was a poor predictor for survival and that there was a poor response rate to intensive chemotherapy (CTx) for sAML with a prior history of HMA prompted us to investigate the role of active treatment in patients with sAML evolving from MDS-HTF (sAML/ MDS-HTF). 8,9 None of the prior studies have analyzed the impact of SCT on the survival of patients with sAML/MDS-HTF, although one group reported a poor outcome in patients with HTF in whom AZA was administered for sAML. 10 The aim of the present study was to evaluate the influences of therapeutic modalities on the survival of patients with sAML/MDS-HTF by analyzing clinical outcomes according to the treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent reports have shown a poor prognosis for patients with MDS experiencing HTF (MDS-HTF). Jabbour et al 8 reported that patients with HTF following DAC treatment had a median survival of 4.3 months. Prebet et al 8 showed a median survival of 5.6 months and a 2-year survival probability of 15.0% in patients with HTF following AZA treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognosis after azacitidine failure is poor both in MDS patients (Prébet et al. 2011), and in AML patients progressed from MDS (Prébet et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Small case series have shown that decitabine treatment after azacitidine failure yields modest responses (ORR: 0%-28%) that are generally short lived [48,[50][51][52][53]; however, this is not currently standard treatment practice. The current standard of care for patients with MDS who have not responded after at least six cycles of azacitidine treatment is to consider clinical trials [48,49] or proceed with SCT [51].…”
Section: Azacitidine For Injectionmentioning
confidence: 99%